Bayesian inference for the mixed-frequency VAR model - Paul Viefers (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this paper a mixed-frequency VAR à la Mariano & Murasawa (2004) with Markov regime switching in the parameters is estimated by Bayesian inference. Unlike earlier studies, that used the pseuo-EM algorithm of Dempster, Laird & Rubin (1977) to estimate the model, this paper describes how to make use of recent advances in Bayesian inference on mixture models. This way, one is able to surmount some well-known issues connected to inference on mixture models, e.g. the label switching problem. The paper features a numerical simulation study to gauge the model performance in terms of convergence to true parameter values and a small empirical example involving US business cycles.
Keywords: C32; C38; E32; E37; E51; 330; Markov mixture models; Label switching; Bayesian VAR; Mixed frequencies